2004
DOI: 10.1176/appi.ps.55.12.1397
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mood Disorders Among Juvenile Offenders

Abstract: Juvenile detainees have a constitutional right to needed mental health treatment. More comprehensive mental health services are required to ensure that juvenile offenders with mental illness are identified and cared for appropriately. Doing so not only will alleviate painful symptoms but may also contribute significantly to improvements in psychosocial functioning, interpersonal relations, and school performance and to decreases in delinquent, disruptive, and suicidal behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 90 publications
0
31
0
1
Order By: Relevance
“…Taking our findings of lower self-esteem in the group with severe delinquency into account, one may assume that this offender type might have compensated feelings of inadequacy with delinquent activities with other juveniles. Furthermore, features of irritability might also have played a role in these adolescents with both delinquency and depressive symptoms [9,12]. However, causal relations are not yet clear and depression can also result from criminal behaviour or its consequences such as being arrested [9,42,43] or facing court examination and penal consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking our findings of lower self-esteem in the group with severe delinquency into account, one may assume that this offender type might have compensated feelings of inadequacy with delinquent activities with other juveniles. Furthermore, features of irritability might also have played a role in these adolescents with both delinquency and depressive symptoms [9,12]. However, causal relations are not yet clear and depression can also result from criminal behaviour or its consequences such as being arrested [9,42,43] or facing court examination and penal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Depression increased with the frequency of delinquent behaviour in boys as well as in girls. Mood disorders were frequently seen both in incarcerated juvenile delinquents and in juveniles with mixed detention situations with prevalence rates varying between 10 to 78% [5,12]. Furthermore, high scores of adjustment disorders with depressed mood were also observed in outpatient samples [10] and high rates of depressive symptoms based on the Beck’s Depression Inventory [13] were reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Drerup, Croysdale, and Hoffmann (2008) studied over 600 youth in the juvenile justice system and estimated that 92% of males and 97% of females had at least one DSM diagnosis. Ryan and Redding (2004) reviewed articles about the prevalence of mood disorders in the juvenile offender populations published after 1980. They found that prevalence rates for mood disorders varied across studies from 17-78%.…”
Section: Juvenile Justice Needsmentioning
confidence: 99%
“…The role of families (Cernkovich et al 2008;Cottle et al 2001), mental health issues (Cottle et al 2001;Drerup et al 2008;Ryan and Redding 2004), poor social skills (Cottle et al 2001), and inadequate school performance (Cottle et al 2001;Sweeten et al 2009) have all been documented as risk factors for general delinquency. For the purpose of the literature review, however, emphasis is placed on the risk factors related to adolescent girls and juvenile prostitution.…”
Section: Literature Reviewmentioning
confidence: 99%